MEOR ABDUL RAHMAN: KONSEP TEMPUR SENI GAYONG DAN INOVASI SILAT MELAYU - Wan Hasbullah, Wan Mohd Dasuki (Jurnal Pengajian Melayu (JOMAS), 2018)
Silat takes on different meanings in accordance with the understanding and philosophy of its particular disciplines, including aspects of combat skills. Over past decades, the focus of research on silat are on the art itself and its philosophical mysticism. However, there is very little that addresses the deeper meaning within silat movements. Using an ethnohistorical approach, this article is an attempt to investigate the concept of combat in Malay martial arts, and its importance to the development of the concept and the institution of silat itself – as illustrated by the case of Dato’ Meor Abdul Rahman and seni gayong. Based on archive and library research, this article suggests that in the seni gayong school, the concept of combat effectiveness is emphasized at the very beginning of training, based on their understanding of the concept of ‘gayong’. This concept is used to redefine the meaning of Malay silat so that it alignes with current situations. It is also seen as crucial because it helps define the needs of technical expertise in the Malay art of war and is perceived as helping to achieve a level of patriotism within the discipline. Thus, this article aims to provide insights into some aspects of technical knowledge Malay silat practitioners which need to be studied and preserved as a legacy of traditional wisdom. Keywords: Silat, concept of fighting, Malay martial arts, technical knowledge, patriotism.